RUSSIAN LANGUAGE AS A REFLECTION OF THE PECULIARITIES OF NATIONAL THINKING - kadhim Majdi, Hussein (Al-Adab Journal, 2021)
The article notes the interrelation of language, culture and thinking. Some stable linguistic expressions that convey the meanings of specific phenomena in Russian and English are considered and reflect the phenomena of the surrounding world through the features of the transfer of values inherent in a particular country. The analysis of influence of mentality on features of national thinking is given. The factors that determine the formation of the national mentality and mentality of the Russian people are described. Features of features of Russian people in comparison with features of the American people are resulted.